Pemberdayaan Lansia dalam Penerapan Lima Pilar Diabetes Melitus di Puskesmas Tajinan Kabupaten Malang - Monika Luhung; Ifa Pannya Sakti; Eli Lea Widhia Purwandhani (Malahayati Nursing Journal, 2025)
ABSTRACT Diabetes mellitus is one of the chronic diseases that can lead to serious complications across all age groups, including the elderly. Various efforts have been made to prevent complications, such as patients' adherence to the five pillars of diabetes mellitus. It is crucial for elderly individuals with diabetes mellitus to have good knowledge as it forms the basis for their thinking and actions. Therefore, empowering the elderly to have a good understanding of the five pillars of diabetes mellitus is necessary. This community service aims to enhance the elderly's understanding of the five pillars of diabetes mellitus. The method used in this community service is empowerment of the elderly through education on the five pillars of diabetes mellitus, utilizing leaflets and PowerPoint presentations. The participants are elderly individuals with diabetes mellitus residing in the Tajinan Malang Community Health Center's service area, who are already members of the prolanis program totaling 25 people. The service activities consist of: 1. Preparation Stage: Obtaining permits, preparing materials, and questionnaires. 2. Implementation Stage: Starting with a pre-test followed by education on diabetes mellitus and its five pillars. 3.Evaluation Stage: Assessing the elderly's understanding using a questionnaire with 10 questions. Each correct answer scores 1point, incorrect answers score 0 points. The average scores of the pre-test and post-test are calculated to measure the improvement in the elderly's knowledge before and after the education. The results obtained from this community service project are as follows: Pre-test results: Knowledge categorized as Fair (60-75%): 44% (11 individuals); Knowledge categorized as Poor (≤ 60%): 56% (14 individuals), Post-test results: Knowledge categorized as Good (76-100%): 32% (8 individuals); Knowledge categorized as Fair (60-75%): 64% (16 individuals); Knowledge categorized as Poor (≤ 60%): 4% (1 individual). The average pre-test knowledge score showed that 56% (14 individuals) had poor knowledge. This improved significantly in the post-test, where the average knowledge score categorized as Fair increased to 64% (16 individuals). Continuous support and guidance for the elderly by the Tajinan Community Health Center's health cadres is essential. Keywords: Empowerment, Elderly, Five Pillars of Diabetes Mellitus     ABSTRAK Diabetes melitus merupakan salah penyakit kronis yang dapat menyebabkan komplikasi serius pada semua tingkat usia termasuk lansia. Berbagai upaya dilakukan untuk mencegah komplikasi seperti ketaatan penderita dalam melaksanakan prinsip lima pilar diabetes melitus. Penting bagi lansia pengidap diabetes melitus mempunya pengetahuan yang baik karena menjadi dasar seseorang dalam berfikir dan bertindak, sehingga diperlukan pemberdayaan lansia agar mempunyai pemahaman pengetahuan yang baik tentang lima pilar diabetes melitus. Pengabdian kepada masyarakat ini bertujuan meningkatkan pemahaman lansia tentang lima pilar diabetes melitus. Metode yang digunakan dalam pengabdian masyarakat ini adalah pemberdayaan lansia melalui edukasi tentang lima pilar diabetes melitus, dengan menggunakan media leaflet dan power point. Peserta adalah lansia diabetes melitus yang tinggal di Wilayah Kerja Puskesmas Tajinan Malang dan sudah menjadi anggota prolanis yang berjumlah 25 orang. Kegiatan pengabdian terdiri dari: Tahap pertama: tahap persiapan: mengurus perijinan, menyiapkan media dan kuisioner. Tahap kedua: pelaksanaan diawali pre tes dilanjutkan edukasi tentang diabetes melitus dan lima pilar diabetes melitus. Tahap ketiga: melakukan evaluasi terhadap pemahaman lansia, evaluasi menggunakan kuisioner berisi 10 butir pertanyaan dan memberikan skor 1 jika jawaban benar, skor 0 jika jawaban salah bobot, selanjutknya dihitung rata-rata pre tes dan pos tes untuk melihat peningkatan pengetahuan lansia antara sebelum dan sesudah edukasi. Hasil yang diperoleh dari kegiatan pengabdian masyarakat ini yaitu: pre tes pengetahuan kategori Cukup dengan nilai 60-75 % adalah 44 %(11 orang), dan pengetahuan kategori Kurang dengan nilai ≤ 60 % adalah 56 % (14 orang). Hasil posttest pengetahuan kategori Baik dengan nilai 76-100 % adalah 32 % (8 orang), Pengetahuan kategori Cukup dengan nilai 60-75 % adalah 64 % (16 orang) dan Pengetahuan kategori Kurang dengan nilai ≤ 60 % adalah 4 % (1 orang). Rata-rata hasil pretest:pengetahuan responden pada kategori kurang 56 % (14 orang), menjadi meningkat dengan rata-rata hasil posttest: pengetahuan responden kategori Cukup 64 % (16 orang). Perlu dilakukan pendampingan lansia secara berkesinambungan dari kader Kesehatan Puskesmas Tajinan. Kata Kunci: Pemberdayaan, Lansia, Lima Pilar Diabetes Melitus